Booklet Development Based Research on the Diversity of Insects on Solanaceae as a Suplement of Biology Teaching Materials in High School (Journal of Innovative Science Education, 2018)
Booklet research-based is a teaching material which contains an important information followed by the condition of pictures around students’ environment as like teaching material which is expected by curriculum 2013. This study aims at identifying insect diversity on solanaceae plants in Wirapanjunan-Kandanghaur as a supplement of biology teaching material in high school and analyzing the worthiness of booklet itself. The method of this research used a development which is adopted from ADDIE instructional model The data were taken from a field research about insect diversity on solanaceae plants and booklet worthiness data by the experts of media and content of material, effectiveness booklet viewed from the N-gain students, and the response teacher and students. The result of this study showed that the index of insect diversity on solanaceae plants based on the equality of Shanon-Wiener was obtained 0.30 which showed low level of insect diversity. It was concluded that booklet research-based in insect diversity on solanaceae plants was worthy as a supplement of biology teaching material in high school because it obtained 93.30% which including of very valid criteria given by the experts, students' cognitive learning outcomes were seen from the N-gain score of an average of 0.68 'medium' criteria and obtained the positive response from teacher and student with score of 86.79% which including of very worthy. This research is useful for identifying insect diversity which was potentially as the resources of learning biology.